2010
DOI: 10.1590/s0004-28032010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotrophic factors reduce hepatic fibrosis in rats

Abstract: Taken together, these results suggest the potential therapeutic use of this hepatotrophic factors solution to treat chronic liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…Quantification was performed in ten different histological fields of greater collagen deposition of the same histological section considering the heterogeneous distribution of injury in the samples and the different damage patterns 20. This criterion was standardized for all animals in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification was performed in ten different histological fields of greater collagen deposition of the same histological section considering the heterogeneous distribution of injury in the samples and the different damage patterns 20. This criterion was standardized for all animals in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…The collagen content is typically reported as the percentage of red-stained fibers (Dias et al 2008). The mean percentage of the fibrous area from the 5 histologic sections obtained from 1 rat is equivalent to the volumetric proportion (VP) of collagen fibres in the liver of this rat (Cogliati et al 2010). The following 2 types of comparisons for VP were performed: intergroup comparison (between samples from the rats of the PH þ NHF group and those from the rats of the PH þ S groups after euthanasia) and intragroup comparison (between samples from the same rat in each respective group after hepatectomy and after euthanasia).…”
Section: Quantification Of Collagen and Immunohistochemistrymentioning
confidence: 99%
“…In fact, it has been demonstrated that the in vivo administration of NHF has a strong ability to accelerate and augment cellular proliferation as well as the growth of normal (Parra et al 1994(Parra et al , 1995, fibrotic (Cogliati et al 2010), and cirrhotic (Guerra et al 2009) liver tissues. Moreover, in fibrotic or cirrhotic livers, NHF treatment causes a reduction in the amount of tissue collagen and an improvement in the liver morphology and function (Cogliati et al 2010;Guerra et al 2009;Parra et al 1996). Furthermore, hepatocyte regeneration often results in the regression of liver cirrhosis (Kawada 2011).…”
Section: Introductionmentioning
confidence: 99%
“…De fato, a administração in vivo destes fatores demonstra a sua forte capacidade de acelerar e aumentar a proliferação celular e o crescimento de fígados normais (Parra et al, 1995a;Parra et al, 1995b;Cogliati, 2005;Aloia et al, 2010), fibróticos e cirróticos (Guerra et al, 2009), o que aumenta a proporção de parênquima em relação ao estroma. Além disso, em fígados com fibrose ou cirrose, os FHN também resultam em uma redução na quantidade tecidual de colágeno, facilitando o acesso das células à nutrição e oxigenação sanguínea, acompanhada por uma melhoria morfológica e funcional (Parra et al, 1982;Guerra et al,2009;Cogliati et al, 2010 …”
Section: Descriptorsunclassified
“…De fato, a administração in vivo destes fatores mostrou uma forte capacidade de acelerar e aumentar a proliferação celular e o crescimento de fígados normais (Parra et al, 1994;Parra et al, 1995b;Cogliati, 2005;Aloia et al, 2010), fibróticos e cirróticos (Guerra et al, 2009 (Parra, 1982;Guerra et al, 2009;Cogliati et al,2010). O uso de FHN promove um estímulo no fígado comparável ao da HP de 70% (Parra et al, 1996).…”
Section: Revisão De Literaturaunclassified